Urban and social resilience—the role of cities and civil society organizations in the Search and Rescue system in the Mediterranean - Trombetta, Isabella (Frontiers in Political Science, 2024)
Search and Rescue (SAR) in the Central Mediterranean has been at the center of the European debate on migration management of the past decade. In response to the challenges posed by maritime rescue operations, European governments have increasingly centralized their efforts through Frontex operations, departing from the previous collaborative framework with SAR NGOs that was established in the aftermath of the Lampedusa shipwreck. The political discourse has predominantly focused on the designation and definition of a Port of Safety, sidelining the imperative need for an effective SAR infrastructure, leading to life-threatening impasses at sea, and also leading to the complete disregard for the agency and will of cities. While the cooperation between governments, cities, and civil society organizations has been at the center of successful decentralized migration management efforts on land, a contrasting trend of centralization and diminished cooperation has emerged at sea in the Central Mediterranean. The article argues that the European Union’s shift from SAR-oriented efforts to border management has resulted in heightened inefficiencies within the Mediterranean SAR infrastructure. This inefficiency is attributed to the diminished collaboration with NGOs and local entities. Utilizing the category of resilience as a theoretical framework of migration management, the article will address the role of cities and NGOs in the creation of a coordinated SAR system in the Mediterranean.